The Role of Inferent Hormones on Gonad Maturity Index and Growth of Ambon Betok Fish (Chrysiptera cyanea) - Melani Andi; Muhammad Irfan; Juharni Juharni (Agrikan: Jurnal Agribisnis Perikanan, 2020)
One type of marine ornamental fish that can be developed through cultivation is betok Ambon fish. Cultivation of this fish is quite profitable, and easy to maintain. To maintain the sustainability and sustainability of Betok Ambon fish farming, one way to take is to understand and know the growth and reproduction aspects of this type of fish through the provision of inferent hormones appropriately. Review article This aims to reveal the role of the inferent hormone on the aspects of reproduction and growth of Betok Ambon fish. Reproduction is the reproduction process in living things including Betok Ambon fish. The number of eggs produced by Betok Ambon fish varies between 900 and 3,500. Inferent hormone is one type of reproductive hormone that functions to spur and accelerate the level of gonad maturity in animals including fish. The determination of the inferent hormone dosage is based on the determination of the inferent dose in fish, generally around 10 mg - 80 mg or about 0.1 ml - 0.8 ml. Generally, fish that are given inferent hormone at a dose of 40-60 mg / l can increase the gonad maturity index by 25%, in betok Ambon fish by 30%. Inferent hormone doses around 20-40 mg can increase the growth and survival of ambon betok fish.